Optimalisasi Potensi Ekonomi Masyarakat Melalui Budidaya Jamur Tiram - Waris, Waris; Khasanah, Nurul (LP2M of Institute for Research and Community Services - UIN Walisongo, 2018)
This service research aims to open up the entrepreneurial spirit of Mitir community. The development of entrepreneurial spirit will automatically reduce the unemployment class and the working class in Mitir. With the emergence of oyster mushroom entrepreneurs, it is expected to increase the income of the community. The increasing income of the community is related to the increasing level of education of the younger generation in the country. If the level of education has begun to increase, the poverty rate in the following year will be gradually reduced. Through this paper, it is concluded that the presence of outside agents is very necessary for Mitir community. The agent serves to provide knowledge about the cultivation of oyster. With the presence of the agents, will be able to cut people mindset who tend to take it for granted, so that the community have open opportunities to achieve their own desired goals.Penelitian pengabdian ini bertujuan untuk membuka jiwa wirausaha masyarakat dusun Mitir. Berkembangnya jiwa wirausaha akan secara otomatis memangkas kelas pengangguran, kelas buruh di dusun Mitir. Nantinya dengan banyak munculnya wirausahawan jamur tiram maka pendapatan masyarakat meningkat. Peningkatan pendapatan masyarakat berelasi dengan meningkatnya tingkat pendidikan generasi muda di dusun Mitir. Jika tingkat pendidikan sudah mulai mengalami peningkatan maka secara perlahan angka kemiskinan ditahun berikutnya sedikit dapat dikurangi. Melalui tulisan ini disimpulkan adanya agen dari luar sangat diperlukan bagi masyarakat dsn. Mitir. Agen berfungsi untuk memberikan pengetahuan tentang budidaya jamur tiram. Dengan adanya agen akan dapat memotong mata rantai pola pikir masyarakat yang cenderung take it for granted, sehingga masyarakat terbuka peluangnya untuk mencapai tujuan yang dikehendaki sendiri.